Modification of nylon 66/graphene nanoplatelet composites via electron beam irradiation - Abd Manaf, Mohd Edeerozey; Shueb, Mohammed Iqbal; Mohamad, Noraiham; Abdullah Sani, Nurhernida; Alkaseh, Adel Ali (Microscopy Society of Malaysia, 2022)
As electrical and electronic devices are becoming an integral part of our life, problems related to electromagnetic interference (EMI) have increased. EMI shielding therefore becomes necessary as to protect vulnerable components within the electric and electronic devices from any interference. As shielding materials, polymer-based composites are highly promising to substitute metal-based materials due to their unique features such as light weight, flexible and excellent corrosion resistance. In this study, we aim to enhance electrical conductivity and shielding effectiveness of nylon 66 composites by improving the dispersion of graphene nanoplatelets (GNP) in the polymer matrix via silane functionalization and electron beam irradiation techniques. Silane treatment of GNP was found to significantly improve the electrical conductivity of the composites with a remarkable increase of 10 orders of magnitude from 10-13 to 10-3 Sm-1. However, no improvement in the shielding effectiveness was observed. Subsequent exposure to electron beam irradiation at 50 kGy and 100 kGy dosage was found to effectively improve EMI shielding effectiveness over a frequency range of 0.5–18 GHz. Microscopic observation indicated changes in GNP layers of the irradiated samples. Multi-layered GNP was found in the non-irradiated, whereas more single layered GNP sheets were observed in the samples irradiated with 50 kGy and 100 kGy dosage of electron beam.